Virtualização museal: website da Casa Museu I João Luiz Pozzobon em São João do Polêsine, RS. - Poll, Estevan Garcia (2022)
The present dissertation, inserted in the History and Cultural Heritage Research Line, aimed to design a website for the Casa Museu I João Luiz Pozzobon, located in São João do Polêsine/RS, one of the territories of the Quarta Colônia Geopark, as one of the resources/means to supply the demand of that place of memory, regarding its valorization and virtual dissemination. With that, this type of technological resource that results in the final product of this study, presents research results, as a summarized synthesis of the life of João Luiz Pozzobon, especially in the phase in which he lived in his family's house and, in parallel, the context of Italian immigration in the region of Quarta Colônia do RS. Thus, the website presents texts, photos, videos and reports about the life of João Luiz Pozzobon, his house, the local landscape space, the customs of the time, among other contents that not only promote Casa Museu I, but make the visitation of the museum consistent and informative, contributing to promoting tourism, disseminating the cultural and historical values stored in Casa Museu I and, thus, contributing to regional social and economic development. This product was supported by the Municipality of São João do Polêsine, the Associação Amigos da Casa Museu I João Luiz Pozzobon and the Instituto Secular dos Padres de Schoenstatt.